Behaviour of Textile-Reinforced Concrete Beams versus Steel-Reinforced Concrete Beams - Fahed Alrshoudi (Advances in Civil Engineering)
There has been a rising interest in utilising textile reinforcement such as carbon tows in constructing concrete components to enhance the performance of conventional reinforced concrete. Textile-reinforced concrete (TRC) has been used as a construction material mostly as primary reinforcement. However, the structural performance of TRC members has not been investigated in depth. Therefore, to better understand TRC beams’ behaviour under bending load, a widespread experimental investigation was conducted. The results of tensile stress-strain, load-deflection, moment-curvature, and tension stiffening behaviours of TRC beams were associated with conventional steel-reinforced concrete (SRC) beams. In this study, the four-point bending and tensile strength tests were performed. The results revealed that, unlike the stress-strain behaviour observed in steel, textile reinforcement does not exhibit yielding strain. The flexural behaviour of TRC beams shows no similarity to that of SRC beams at postcracking formation. Besides, the moment capacity and tension stiffening of TRC beams were found 56% and 7 times higher than those of SRC beams, respectively. Therefore, in light of these results, it can be said that TRC beams behaviour differs from that of SRC beams.